Fear of Dementia and the Obligation to Provide Aggregate Research Results to Study Participants. (October 2022) - Graham, Mackenzie; Farina, Francesca; Ritchie, Craig W.; Lawlor, Brian; Naci, Lorina
Abstract: A general obligation to make aggregate research results available to participants has been widely supported in the bioethics literature. However, dementia research presents several challenges to this perspective, particularly because of the fear associated with developing dementia. The authors argue that considerations of respect for persons, beneficence, and justice fail to justify an obligation to make aggregate research results available to participants in dementia research. Nevertheless, there are positive reasons in favor of making aggregate research results available; when the decision is made to do so, it is critical that a clear strategy for communicating results is developed, including what support will be provided to participants receiving aggregate research results.